The SPD in the Bonn republic : a socialist party modernizes - Kent Schellenger, Harold (The Hague : Martinus Nijhoff, 1968)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Sozialdemokratische Partei Deutschlands (SPD).; socialistische partijen; Duitsland